A new species of small and highly abbreviated caecilian (Gymnophiona: Indotyphlidae) from the Seychelles island of Praslin, and a recharacterization of Hypogeophis brevis Boulenger, 1911 - Maddock, Simon T.; Wilkinson, Mark; Nussbaum, Ronald A.; Gower, David J. (Zootaxa, 2017)
A new species of indotyphlid caecilian amphibian, Hypogeophis pti sp. nov., is described based on a series of specimens from the Seychelles island of Praslin. The type series was collected in 2013 and 2014, and a referred specimen previously identified as H. brevis Boulenger, 1911 was collected from an unspecified Seychelles locality in 1957. The new species most closely resembles the Seychelles endemic Hypogeophis brevis in being short (maximum known total length in life ca. 120 mm) and long snouted, but differs by having a less anteriorly positioned tentacular aperture and fewer primary annuli and vertebrae. In having only 67–69 vertebrae, H. pti sp. nov. is the most abbreviated extant species of caecilian reported to date.